2008
DOI: 10.1590/s0100-39842008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Medida do comprimento do osso nasal entre 11 e 15 semanas de gestação em uma população brasileira: estudo preliminar

Abstract: Fetal nasal bone length in the period between 11 and 15 gestational week Cicero et al.(3) have evidenced that the nasal bone was absent in 43 of 59 (73%) fetuses with trisomy 21, and in three of 603 (0.5%) chromosomically normal fetuses between the 11th and 14th gestational weeks. In a recent study, the addition of the nasal bone evaluation to the measurement of nuchal translucency (NT) and maternal biochemical serum screening maintained the rate of detection of trisomy 21 at 90%, however reduced the false p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Our study showed that the incidence of hypoplasia or absent nasal bone is low among normal fetuses of Thai women. This is consistent with previous reports [9,10,11,15]. Another possible cause for the difference in the incidence of absent nasal bones was a technical factor or error.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study showed that the incidence of hypoplasia or absent nasal bone is low among normal fetuses of Thai women. This is consistent with previous reports [9,10,11,15]. Another possible cause for the difference in the incidence of absent nasal bones was a technical factor or error.…”
Section: Discussionsupporting
confidence: 93%
“…NBLs in our Thai population are similar to those reported for Korean and Latin-American populations, but differ from those reported for Caucasian, African-American and Chinese populations [10,13,15,16,17,18] as shown in table 1. Our study’s results correlate with studies of NBL in Thai population in the second trimester that showed significant differences in the median and 5th percentile NBL between white, African-American, and Thai populations [19,20].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Such findings coincided with those of Getty (1986) and Lana et al (2012). In contrast, in humans, the nasal bone is small and rectangular (PUTZ; PABST, 1995;COSSI et al, 2008).…”
Section: Resultsmentioning
confidence: 99%